ANALISIS LEVERAGE, UKURAN PERUSAHAAN, GOOD CORPORATE GOVERNANCE PADA MANAJEMEN LABA DENGAN STRUKTUR MODAL SEBAGAI VARIABLE MODERASI - Anindya Aldhira Putri (Jurnal Akuntansi Trisakti, 2020)
The purpose of this analysis is to find the influence of leverage, company size, good corporate governance on earnings management with capital structure as the moderating variable. The sample of this research using the subsector of manufacture sector which is the foods and beverage subsector, from 2016 until 2018, with a requirement where the companies are listed in IDX. The companies samples of this research are 18 companies, with total of 54. The data of the research was processed by the SPSS.The final summary of the research is that, leverage doesn’t have any effect on earning management. As well as company size doesn’t any effect on earnings management because the bigger size of the company the lowest it is for the management to do the practice of earnings management, because their shareholders and creditors are critical on their report. Good corporate governance with an indicator of independent commissioner, board of directors, and internal committee also have a negative effect on earning management. In this research, capital structure weakens the effect of good corporate governance on earning management.